TINJAUAN VISUAL TERHADAP ILUSTRASI KEMASAN BOTOL AQUA 600ML “LABEL KHUSUS TEMUKAN INDONESIAMU” - Febriani Saputri; hendra afriwan (Universitas Negeri Padang, 2020)
This study was created by the writer with the aim of describing the meaning and also the cultural values contained in the Aqua packaging illustration of the special label